Acknowledgement to Editors and Scientific Referees 2020 - Matheus Fernando Manzolli Ballestero; Alexandre Casagrande Canheu; Alexandre Varella Giannetti; Aline Saré de Melo; Angelo Raimundo da Silva; Artur Henrique Galvão Bruno da Cunha; Carlos Umberto Pereira; Eduardo Jucá; Jose Roberto Tude Melo; Leopoldo Mandic Furtado; Luciano Lopes Furlanetti; Marcelo Volpon Santos; et al. (Brazilian Society for Pediatric Neurosurgery, 2020)
A scientific journal's greatest responsibility is to ensure that all contributions accepted for publications are rigorously but fairly reviewed. The Editor-in-Chief and Archives of Pediatric Neurosurgery gratefully acknowledge the qualified and regular collaboration of renowned medical doctors and scientists who kindly devoted their time to constructively review the submitted articles. Their expertise and invaluable assistance contributed to maintain a high scientific standard for APN. We are thus indebted to the Editorial Board members and the following experts who reviewed papers and completed the peer-reviewing process within 2020.